5-HT2CR Blockade in the Amygdala Conveys Analgesic Efficacy to SSRIs in a Rat Model of Arthritis Pain. (12th August 2013) - Grégoire, Stéphanie; Neugebauer, Volker
Background: Pain, including arthritic pain, has a negative affective component and is often associated with anxiety and depression. However, selective serotonin reuptake inhibitor antidepressants (SSRIs) show limited effectiveness in pain. The amygdala plays a key role in the emotional-affective component of pain, pain modulation and affective disorders. Neuroplasticity in the basolateral and central amygdala (BLA and CeA, respectively) correlate positively with pain behaviors. Evidence suggests that serotonin receptor subtype 5-HT2C R in the amygdala contributes critically to anxiogenic behavior and anxiety disorders. In this study, we tested the hypothesis that 5-HT2C R in the amygdala accounts for the limited effectiveness of SSRIs in reducing pain behaviors and that 5-HT2C R blockade in the amygdala renders SSRIs effective. Results: Nocifensive reflexes, vocalizations and anxiety-like behavior were measured in adult male Sprague-Dawley rats. Behavioral experiments were done in sham controls and in rats with arthritis induced by kaolin/carrageenan injections into one knee joint. Rats received a systemic (i.p.) administration of an SSRI (fluvoxamine, 30 mg/kg) or vehicle (sterile saline) and stereotaxic application of a selective 5-HT2C R antagonist (SB242084, 10 μM) or vehicle (ACSF) into BLA or CeA by microdialysis. Compared to shams, arthritic rats showed decreased hindlimb withdrawa thresholds (increased reflexes), increased duration of audible and ultrasonic vocalizations, and decreased open-arm choices in the elevated plus maze test suggesting anxiety-like behavior. Fluvoxamine (i.p.) or SB242084 (intra-BLA) alone had no significant effect, but their combination inhibited the pain-related increase of vocalizations and anxiety-like behavior without affecting spinal reflexes. SB242084 applied into the CeA in combination with systemic fluvoxamine had no effect on vocalizations and spinal reflexes. Conclusions: The data suggest that 5-HT2C R in the amygdala, especially in the BLA, limits the effectiveness of SSRIs to inhibit pain-related emotional-affective behaviors.